OWASP top 10 - Dennison, Justin; Lowrie, Daniel (Packt Publishing, 2024)
Embark on a journey to master web application security by exploring the OWASP Top 10 vulnerabilities. This course starts with an overview, setting the stage for a detailed look at each vulnerability. You will first learn to exploit common security flaws, gaining insights into the attacker's perspective. Next, you'll discover methods to fix these vulnerabilities, implementing robust security measures to protect your applications. Each section concludes with techniques to verify the fixes, ensuring your applications remain secure. Throughout the course, you'll tackle various security issues such as broken access control, cryptographic failures, injection attacks, and insecure design. Each topic is broken down into manageable sections, with dedicated videos for exploiting, fixing, and verifying vulnerabilities. This structured approach ensures you build a solid understanding of each concept before moving on. Designed for web developers, security professionals, and IT specialists, this course requires a basic understanding of web technologies and programming. Whether you're looking to enhance your security skills or secure your organization's applications, this course provides the knowledge and practical skills needed to stay ahead in the ever-evolving field of web security.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Application software -- Security measures; Internet of things; Logiciels d'application; Sécurité; Mesures; Internet des objets; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet